2008
DOI: 10.1210/jc.2008-0104
|View full text |Cite|
|
Sign up to set email alerts
|

Case Detection, Diagnosis, and Treatment of Patients with Primary Aldosteronism: An Endocrine Society Clinical Practice Guideline

Abstract: We recommend case detection of primary aldosteronism be sought in higher risk groups of hypertensive patients and those with hypokalemia by determining the aldosterone-renin ratio under standard conditions and that the condition be confirmed/excluded by one of four commonly used confirmatory tests. We recommend that all patients with primary aldosteronism undergo adrenal computed tomography as the initial study in subtype testing and to exclude adrenocortical carcinoma. We recommend the presence of a unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
1,295
3
63

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,422 publications
(1,376 citation statements)
references
References 122 publications
15
1,295
3
63
Order By: Relevance
“…36 Correct diagnosis and treatment of PA can not only lead to cure of hypertension in patients with unilateral forms of PA, but can also prevent and reverse organ deterioration independent of aldosterone effects on BP. 37 The prevalence of PA is similar in men and women, but estrogen and progesterone can affect aldosterone and renin levels and, consequently, can interfere with the investigation of PA.…”
Section: Secondary Hypertension In Womenmentioning
confidence: 99%
“…36 Correct diagnosis and treatment of PA can not only lead to cure of hypertension in patients with unilateral forms of PA, but can also prevent and reverse organ deterioration independent of aldosterone effects on BP. 37 The prevalence of PA is similar in men and women, but estrogen and progesterone can affect aldosterone and renin levels and, consequently, can interfere with the investigation of PA.…”
Section: Secondary Hypertension In Womenmentioning
confidence: 99%
“…1 Using the aldosteroneto-renin ratio (ARR) as a screening tool, several studies found that PA is more frequent than previously assumed, affecting 1-13% of hypertensive individuals. [2][3][4][5][6] The different frequency found in these studies is because of the use of different screening tools, study designs and various study populations.…”
Section: Introductionmentioning
confidence: 99%
“…PA was diagnosed in accordance with the cutoff established in our laboratory and the Endocrine Society Practice Guidelines aldosterone concentration (ARR > 12 ng/l/μU/ml and aldosterone concentration > 50 ng/l after saline infusion) [7]. Seventy-nine patients with suspected PA were assessed by a saline infusion test prospectively.…”
Section: Patients and Test Conditionsmentioning
confidence: 99%
“…The test was performed under standardized test conditions if primary aldosteronism was suspected as outlined in the Clinical Practice Guidelines [7]. Potassium was supplemented when the potassium concentration was below 3.5 mmol/l and interfering antihypertensive medication was changed to non-dihydropyridin calcium channel blockers and alpha-blockers whenever possible.…”
Section: Sodium Infusion Testmentioning
confidence: 99%
See 1 more Smart Citation